2017
DOI: 10.7863/ultra.16.05012
|View full text |Cite
|
Sign up to set email alerts
|

Value of Ultrasonographic Features for Assessing Malignant Potential of Complex Cystic Breast Lesions

Abstract: US is an important adjunct to evaluate the malignant potential of complex cystic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
2
0
5
Order By: Relevance
“…Fatma Kulali et al 15 found that complex C-SNs of the breast are usually predominantly benign nodules with pathology of fibroadenomatoid/fibrocystic changes and malignant nodules with pathology of intraductal papillary carcinomas, and cystic lesions are usually more common with benign lesions. However, C-SNs have a wide probability of malignancy in previous studies (20–40%) 16 , 17 . Although there have been more studies in the last decade to determine the benignity and malignancy of complex cystic nodules of the breast, there is still no consensus on the specific ultrasound features.…”
Section: Discussionmentioning
confidence: 87%
“…Fatma Kulali et al 15 found that complex C-SNs of the breast are usually predominantly benign nodules with pathology of fibroadenomatoid/fibrocystic changes and malignant nodules with pathology of intraductal papillary carcinomas, and cystic lesions are usually more common with benign lesions. However, C-SNs have a wide probability of malignancy in previous studies (20–40%) 16 , 17 . Although there have been more studies in the last decade to determine the benignity and malignancy of complex cystic nodules of the breast, there is still no consensus on the specific ultrasound features.…”
Section: Discussionmentioning
confidence: 87%
“…The malignancy rate of complex cysts was noted as 36% (18/50) 9 . Yao et al 17 have categorized 79 complex breast lesions into four groups according to sonographic findings. Similar to ours, they found malignancy rate was higher in type 3 and 4 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…До дифузної форми можна зарахувати всі види так званих мастопатій, а до вузлової -доброякісні пухлини. Розподіл дисгормональних дисплазій на дифузну та вузлову має практичне значення: хворих із дифузними формами лікують консервативно, а з вузловими -оперативно [33,34].…”
Section: гінекологіяunclassified
“…Це виявляється при пальпації, під час ультразвукового дослідження, на рентгенограмі грудної залози (мамографія). Вирішальне значення для вибору методу лікування має диференційна діагностика, під час якої визначають доброякісне чи злоякісне походження пухлинного вузла [33,35].…”
Section: гінекологіяunclassified
See 1 more Smart Citation